(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Organizations have realized that engaged employees are invaluable assets to an organization. Surveys have been revealing that engagement promotes talent retention and improves organizational performance. Culture of an organization impacts the way interaction happens between people and groups and the way they work with each other. This research intended to throw light on the possible influence organization culture for the adoption of employee engagement practices.